BOOK REVIEW: BIEREENU-NNABUGWU, Makodi (2005) Africa in the March of Civilization: An Outline of African Heritage. - TAMUNOSAKI, Taylor (Socialscientia: Journal of Social Sciences and Humanities, 2019)
The book, Africa in the march of civilization: An outline of African heritage is a scholarly work by Makodi Biereenu-Nnabugwu which provides scholarship with a new vista seeks to redirect academic discourse away from a Eurocentric dominated narration and analysis of African history and social science to an African (and of course more objective) perspective. The author makes an argument against such Eurocentric assertions that Africa had no history and no trace of civilization before their contact with the white man, first during the legitimate trade and later during colonialism (the so called civilizing mission). The author does not just posit that Africa has a history but goes on to assert that it also has a heritage. All other arguments and analysis made in the book by the author is intended to show case and prove this singular position.